The Influence of User-Generated Content (UGC) and Electronic Word-of-Mouth (E-WOM) on Purchasing Decisions through Brand Image At Sens Hotel & Spa Ubud - Kadek Wirahadi Mahartika; Reny Nadlifatin (JURNAL ECONOMINA, 2026)
he Room Occupancy Rate (TPK) of starred and non-starred hotels in Bali Province in the period March 2024 to March 2025 was recorded at 52.71% while non-starred hotels were at 38.44%. This percentage experienced a significant increase in October 2024, where the ROC for starred hotels reached 64.37% and for non-starred hotels 43.94%. This increase indicates post-pandemic recovery and increased tourist interest during the peak season. However, in 2025, the ROC experienced a gradual decline. In February 2025, the estimated ROC for starred hotels showed a figure of ±51.62% and for non-starred hotels ±36.35%, then decreased again in March 2025 to 46.61% for starred hotels and 35.71% for non- starred hotels. This decline shows that even though Bali's hotel industry has recovered, maintaining occupancy levels remains a challenge, especially outside the holiday season. Consumer expectations of digital services and information when choosing accommodations can be one of the causes of these fluctuations. This study aims to examine and analyze the influence of user-generated content (UGC) and electronic word of mouth (E-WOM) on purchasing decisions through brand image as a mediating variable. The analysis method carried out quantitatively by distributing questionnaires which then be analyzed using the Structural Equation Model (SEM). The results of this study indicate that User-Generated Content (UGC), Electronic Word of Mouth (E-WOM), and Brand Image have a positive but insignificant effect on purchase decisions. Furthermore, User-Generated Content (UGC) and Electronic Word of Mouth (E-WOM) have a positive and significant effect on Brand Image. Additionally, User- Generated Content (UGC) and Electronic Word of Mouth (E- WOM) have a positive and significant indirect effect on purchase decisions through Brand Image as a mediating variable.